Evaluation of a New IFN-γ Release Assay for Rapid Diagnosis of Active Tuberculosis in a High-Incidence Setting - Li, Gen; Li, Feng; Zhao, Hui-Min; Wen, Han-Li; Li, Hai-Cong; Li, Chun-Ling; Ji, Ping; Xu, Peng; Wu, Kang; Hu, Zhi-Dong; Lu, Shui-Hua; Lowrie, Douglas B.; et al. (Frontiers in Cellular and Infection Microbiology, 2017)
Blood-based interferon-gamma (IFN-γ) release assays (IGRAs) have been proven to be useful in the diagnosis of Mycobacterium tuberculosis (Mtb) infection. However, IGRAs have not been recommended for clinical practice in most low-income settings due to cost-intensive limitations and shortage of clinical data available. The established T-SPOT.TB assay containing Mtb-specific antigens ESAT-6 and CFP10 are widely used for immunodiagonsis of Mtb infection, but the high cost is one of the restricting factors against its clinical application in the developing countries. More recently, a cost-saving IGRA assay, TS-SPOT, was approved in China. This new assay contains an additional antigen Rv3615c. Rv3615c contains broadly recognized CD4+ and CD8+ epitopes, and T-cell responses to Rv3615c are as specific for Mtb infection as the responses to ESAT-6 and CFP10 in both Mtb-infected humans and M. bovis-infected cattle. Therefore, we assessed the likely effect of inclusion of Rv3615c as stimulus besides ESAT-6 and CFP10 in an IGRA assay and evaluated the performance of TS-SPOT for diagnosis of Mtb infection and active TB compared with T-SPOT.TB. We tested 155 active TB patients, 90 non-TB lung disease patients and 55 healthy individuals. The results presented an improved positive rate for diagnosis of active TB and Mtb infection, that could be attributable to inclusion of Rv3615c in the mixture of stimulatory antigens. The diagnostic efficiency of TS-SPOT assay for active TB was as follows: sensitivity 80.00%, specificity 83.45%, positive predictive value (PPV) 83.78%, negative predictive value (NPV) 83.45%, positive likelihood ratio (LR+) 4.83, and negative likelihood ratio (LR-) 0.24. The results were similar to those of T-SPOT.TB, with an excellent agreement (κ = 0.91, 95% CI: 0.85-0.95) being observed between these two assays. The sensitivities of the TS-SPOT assay varied for patients with different forms of active TB, with the highest sensitivity for patients with culture-positive pulmonary TB (92.16%) and the lowest for those with tuberculosis meningitis (50.00%). Taken together, the current evidence indicates that this new TS-SPOT assay is a useful adjunct to the current tests for rapid diagnosis of active TB and Mtb infection in low-income and high-incidence settings due to its characteristics of cost-effectiveness and high-quality.